2020
DOI: 10.1088/1742-6596/1567/4/042021
|View full text |Cite
|
Sign up to set email alerts
|

Students’ behaviour towards etno-STEM: instruments for students of etno-STEM based science education

Abstract: The learning process that is synergistic with the development of the current era is very necessary. Local wisdom that is aligned with technology is a challenge. Therefore, this study aims at developing a tool which is functioned to measure students’ readiness towards developing instruments related to etno-STEM based Science Education courses. The selected items were given to the expert team for validation. The initial trial of the initial instrument was done using the main component analysis and Cronbach alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…The authors in red cluster simultaneously conducted the research about ethnomedicine-based science learning [22]. Some researches related to local wisdom-based Spermatophyta learning and ethno-science, technology, engineering, and math (STEM)-based science education were carried out by the authors in green cluster and purple cluster [56], [57]. The authors in blue cluster studied regarding local plants as the basic materials of batik natural dyes and local wisdom-based integrative learning model using multimedia animation [58], [59].…”
Section: Co-authorship Analysismentioning
confidence: 99%
“…The authors in red cluster simultaneously conducted the research about ethnomedicine-based science learning [22]. Some researches related to local wisdom-based Spermatophyta learning and ethno-science, technology, engineering, and math (STEM)-based science education were carried out by the authors in green cluster and purple cluster [56], [57]. The authors in blue cluster studied regarding local plants as the basic materials of batik natural dyes and local wisdom-based integrative learning model using multimedia animation [58], [59].…”
Section: Co-authorship Analysismentioning
confidence: 99%
“…Berdasarkan data yang dihasilkan bahwa penggunaan Budaya lokal (Bundengan) dalam pembelajaran gelombang dan bunyi cukup efektif digunakan. Pembelajaran berbasis kekayaan lokal dapat meningkatkan kemampuan literasi sains (Reffiane et al, 2020), dimana budaya lokal termasuk potensi dan kearifan yang dimiliki suatu daerah.…”
Section: Uji Hipotesisunclassified
“…However, Adesoji et al (2019) showed that teachers' awareness of ethnoscience practices in their teaching area is below expectations because it offers an average score (60.34). Even though a synergistic learning process with today's developments is very much needed (Reffiane et al, 2020). There needs to be an attitude that can make teachers aware of the importance of culture in learning.…”
Section: Research Findingsmentioning
confidence: 99%